(untitled) (Journal of Medical Device Technology, 2024)
Chronic wounds among diabetic patients have always been in a concerning state over the past years. The implementation of non-invasive procedures such as ultrasound techniques to accelerate the healing of diabetic wounds is believed to provide impressive benefits in terms of improving cells’ physiology mechanistically. This current study focused on the effect of pulsed-low intensity ultrasound (PLIUS) as a mechanical stimulator for wound healing experiments under a hyperglycemic microenvironment. HSF 1184 cells were first optimized in 6-well plates using several seeding densities. The optimized seeding density, 4 × 105 cells/mL, was used for the scratch assay experiment. PLIUS probe was placed on the center of the scratched cells and treated with several doses for 5 minutes. The percentage of wound closure of HSF 1184 was analyzed using ImageJ software. The results revealed that the cells subjected to ultrasound treatment at a frequency of 1 MHz, intensity of 0.3 W/cm2, and 50% of duty cycle exhibited the greatest extent of wound closure in comparison to the other two ultrasound dosages. In summary, it can be concluded that the utilization of low-intensity therapeutic ultrasound at a frequency of 1 MHz, an intensity of 0.3 W/cm2, and a duty cycle of 50% holds promise for facilitating wound healing under a hyperglycemic microenvironment.